The Clinicopathological Spectrum of Parathyroid Carcinoma - Akirov, Amit; Asa, Sylvia L.; Larouche, Vincent; Mete, Ozgur; Sawka, Anna M.; Jang, Raymond; Ezzat, Shereen (Frontiers in Endocrinology, 2019)
Background: Parathyroid carcinoma is rare, representing <1% of primary hyperparathyroidism cases. . Methods: Retrospective data of patients referred for evaluation of parathyroid disease between 2001 and 2018. The goal was to describe the clinical presentation, histopathologic characteristics, and treatment outcomes. Results: We identified 8 cases of parathyroid carcinoma from the outpatient practice of a quaternary care Endocrine Oncology practice in Toronto, Canada. The clinical presentation was as follows: 5/8 cases (62.5%) of symptomatic hypercalcemia and 3/8 cases (37.5%) of a suspicious thyroid nodule. Hypercalcemia was evident in all 7 cases with pre-operative calcium measurements. Histopathologic features included: vascular invasion in 7/8 cases (87.5%) and immunohistochemical loss of either parafibromin, retinoblastoma, or p27 in all 8 cases. Additional treatment included: external beam radiotherapy in 5/8 cases (62.5%), chemotherapy for 2/8 patients (25%), and additional surgery for 3/8 patients (37.5%). Only 2 patients (25%) had long-term remission following surgical treatment, and the others had either persistent (3 patients) or recurrent disease (3 patients). Five patients developed metastatic disease, all involving lung. In one of two patients treated with Sorafenib there was evidence of regression of lung metastases. One patient died of disease progression. Conclusion: In this series of patients with parathyroid carcinoma largely presenting with symptomatic hypercalcemia and angioinvasive disease, only a minority achieved a durable remission. Lung was the most common site for distant metastases. Surgery has led to remission in two cases, but none of the six patients with persistent or recurrent disease ultimately achieved disease remission in this series.